Efforts of the Indonesian Waqf Board in Bandar Lampung City in Socializing Monetary Waqf Literacy - Nurlela Nurlela; Ulil Albab; Heri Sutopo (ProBisnis : Jurnal Manajemen, 2023)
The role of the Indonesian Waqf Board as an independent institution, born according to the mandate of Law Number 41 of 2004 concerning Waqf, carries a significant responsibility in advancing and developing endowments (Waqf) in Indonesia. This research is a field study employing a qualitative methodology. The approach used is a qualitative descriptive approach. Data collection techniques include observations, interviews, and documentation. Data validation techniques employ source triangulation. The results of this research follow the role of the Indonesian Waqf Board in Bandar Lampung City in disseminating financial waqf literacy that has yet to be maximized, as seen from the achievements or the ongoing activities that have not been consistently implemented. secondly, secondly the challenges faced by the Indonesian Waqf Board in Bandar Lampung City in enhancing financial waqf literacy including a need for a workforce and an available budget. However, if continued as before, it can still be carried out through letter distribution and the creation of brochures, banners and social media.